2015
DOI: 10.1155/2015/159051
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Pentraxin-3 Level in Patients with STEMI and Its Relationship with Heart Failure and Markers of Oxidative Stress

Abstract: Objective. Pentraxin-3 (PTX3) appears to have a cardioprotective effect through a positive influence against postreperfusion damage. This study assesses the prognostic value of PTX3 level and its relationship with clinical parameters and markers of oxidative stress and nitric oxide metabolism in patients with ST-elevation myocardial infarction (STEMI). Methods. Plasma/serum levels of several biomarkers of inflammation and oxidative stress and nitrite/nitrate were assessed upon admission and 24 h after STEMI on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
3
15
1
2
Order By: Relevance
“…A study conducted by Marie Tomandlova et al in 2015 found that high levels of serum PTX3 can predict 1-year mortality of patients with STEMI; these patients are more likely to be afflicted with ventricular dysfunction after MI, causing their mortality to go higher and higher after 1 year [16]. However, both the nature and examined population of the present study differed hugely with their study.…”
Section: Discussioncontrasting
confidence: 62%
“…A study conducted by Marie Tomandlova et al in 2015 found that high levels of serum PTX3 can predict 1-year mortality of patients with STEMI; these patients are more likely to be afflicted with ventricular dysfunction after MI, causing their mortality to go higher and higher after 1 year [16]. However, both the nature and examined population of the present study differed hugely with their study.…”
Section: Discussioncontrasting
confidence: 62%
“…Interestingly, PTX3 plasma levels might be a potentially useful biomarker to predict prognosis as well as to detect inflammatory status in patients with chronic heart failure, e.g. due to cardiac ischemia . The impact of this multifunctional molecule in infectious disease and also during sterile inflammation of the heart makes PTX3 an important regulator of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…8,9) Appropriate prognostic risk stratification may help clinicians better manage patients by assessing mortality risk. Recent studies have been attempting to identify novel biomarkers such as ubiquitin, Gremlin-1, cyclophilin A, pentraxin-3, and heterogeneous nuclear ribonucleoprotein C. [10][11][12] In our study, we enrolled 287 subjects in order to explore the easily measured and complementary long-term prognostic factors ST2, NT-proBNP, and serum sodium in AHF patients receiving standard treatment according to the guideline. Our goals were to clarify the roles of these 3 variables as indicators of AHF prognosis and to investigate the specific cut-off level for risk stratification.…”
mentioning
confidence: 99%